Economic Impacts of AI-Driven Automation in Financial Services - Babatunde Adeyeri, Toluwani (International Journal of Scientific Research and Management (IJSRM), 2024)
Artificial Intelligence (AI)-driven automation is increasingly transforming the financial services industry, promising significant economic benefits such as enhanced efficiency, cost reductions, and improved customer experiences. This research paper delves into the economic impacts of AI-driven automation within this sector, examining both the positive and negative ramifications. The literature review provides a historical context of automation in financial services and discusses contemporary AI technologies like machine learning and robotic process automation that are pivotal in this transformation.The paper identifies several positive economic impacts, including increased productivity, cost savings, enhanced accuracy, and better customer service. However, it also addresses negative impacts, notably job displacement, security and privacy concerns, and economic inequality. Through detailed case studies of major financial institutions that have successfully implemented AI, the research highlights real-world economic outcomes, best practices, and lessons learned.Challenges associated with AI-driven automation, such as technical and operational hurdles, regulatory compliance, and ethical considerations, are thoroughly analyzed. The paper also explores future prospects, suggesting that while AI advancements hold great potential for further transformation of financial services, careful management of long-term economic implications is essential. Policy recommendations include investing in workforce retraining and education to prepare for the evolving job market.This comprehensive study aims to provide a balanced perspective on the economic impacts of AI-driven automation in financial services, offering insights into how the industry can leverage AI for growth and innovation while addressing associated challenges and ensuring a sustainable and inclusive future.